Biocompatibilidade in vivo e eficácia antimicrobiana de produto odontológico nanoestruturado para aplicação endodôntica - Viera, Fabrício Oliveira (2023)
The work addresses the historical use of cresol formalin in endodontics, pointing out its controversies regarding biocompatibility. It proposes the utilization of nanotechnology to develop a nanoparticle of cresol formalin, aiming to enhance its effectiveness and minimize potential negative effects. The study focuses on evaluating in vivo biocompatibility and antimicrobial efficacy of this new nanostructured product for endodontic application. The objectives include nanoparticle preparation and characterization, assessment of hematological, biochemical, and histological parameters in an animal model, as well as analysis of antimicrobial efficacy. The interdisciplinary approach is emphasized, considering diverse areas of knowledge necessary to develop and evaluate the product. The work highlights the importance of nanotechnology in medical treatment innovation, exploring its potential for precision and efficiency. In this study, cresol formalin nanoparticles were prepared and characterized to be incorporated into a pharmaceutical gel form intended for intracanal application in dental treatments. The methodology encompassed meticulous replication of preparation steps, physicochemical characterization of nanoparticles, careful selection of gelling agents like hydroxyethyl cellulose (Natrosol), and incorporation of a preservative, Nipaguard SCE, to maintain efficacy over time. Furthermore, in vivo biocompatibility studies were conducted in rats, evaluating the effects and safety of formulations after implantation. Microbiological tests were also performed to determine the antimicrobial effectiveness of the nanoparticles. This comprehensive process resulted in the formulation of an innovative dental product with the potential to enhance treatment efficacy and quality in dental canals. The assessment of biocompatibility and cytotoxicity of NCTF in gel was conducted in rats. Hematological and biochemical tests showed no significant alterations in the tested groups compared to reference values, indicating that the gel had no negative impacts on the hepatic and renal systems of the rats. Hematological examinations also remained within normal limits, providing a solid foundation for the safety of the gel. Microbiological tests demonstrated that both the nanoformulation and the gel with preservative were effective in inhibiting and destroying microbial growth, including resistant bacteria, suggesting their antimicrobial potential. Histological studies revealed that the tested groups exhibited low-intensity inflammatory reactions, suggesting that the NCTF gel did not induce significant adverse reactions in tissues. In summary, the study demonstrated that the NCTF gel developed based on nanotechnology exhibits stable physicochemical characteristics, biocompatible safety, and antimicrobial potential, showing promising applications in the field of endodontics and dental infection treatment.